2004
DOI: 10.1111/j.1365-3156.2004.01332.x
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of Toxocara canis infection among mountain aboriginal schoolchildren living in contaminated districts in eastern Taiwan

Abstract: SummaryWe conducted a seroepidemiological study of Toxocara canis infection among mountain aboriginal schoolchildren aged 7-12 years living in contaminated districts in eastern Taiwan. To detect sera IgG ( ‡1:64) we used a T. canis larval excretory-secretory antigen-based enzyme-linked immunosorbent assay. A short questionnaire elicited information on the practices of raising dogs, playing with soil, eating raw vegetables, or whether the child normally washed his/her hands before eating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 29 publications
(75 reference statements)
5
33
2
1
Order By: Relevance
“…CHIEFFI et al 10 and SCHANTZ et al 37 , reported a higher frequency of infection in individuals who were in contact with dogs, however, other studies found no association between ownership or professional contact with dogs and Toxocara infection 22,26 . FAN et al 18 observed high seropositive rates in 79.4% of dog owners, and 67.9% in nonowners, suggesting that these two groups are equally at risk of infection. These results are in line with those of WOODRUFF et al 42 who observed that 50% of patients with clinical toxocariasis owned dogs.…”
Section: Discussionmentioning
confidence: 98%
“…CHIEFFI et al 10 and SCHANTZ et al 37 , reported a higher frequency of infection in individuals who were in contact with dogs, however, other studies found no association between ownership or professional contact with dogs and Toxocara infection 22,26 . FAN et al 18 observed high seropositive rates in 79.4% of dog owners, and 67.9% in nonowners, suggesting that these two groups are equally at risk of infection. These results are in line with those of WOODRUFF et al 42 who observed that 50% of patients with clinical toxocariasis owned dogs.…”
Section: Discussionmentioning
confidence: 98%
“…in 38.8 % of healthy children and observed a statistically significant correlation between occurrence of antibodies and low hygiene practices. Fan et al (2004) reported up to 75.6 % of seropositive healthy children living in Taiwan, in an environment contaminated by eggs of Toxocara spp. Kaplan et al (2004) detected a substantially higher seroprevalence in groups of mentally disabled persons (18.8 %) than was that in a sample of healthy individuals (7.1 %).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical manifestation of human toxocariasis is usually asymptomatic (2,4). Nevertheless, visceral larva migrants (VLM) and ocular larva migrants (OLM) as two major syndromes of toxocariasis in human can be detected (6,7). VLM signs are recognized by fever, hepatomegaly, splenomegaly, respiratory symptoms, muscle pain, hypergammaglobulinemia, and eosinophilia (2,7,8).…”
Section: Introductionmentioning
confidence: 99%